Effect of surface carbon-oxygen complexes during NO reduction by coal char. (15th September 2017) - Yan, Wenxia; Li, Songgeng; Fan, Chuigang; Deng, Shuang
Highlights: NO reduction and simultaneous CO formation are focused. Textural and structural properties of the coal chars are examined. Thermally stable C–O species favor NO reduction and suppress CO formation. Two reaction mechanisms are put forward. Abstract: Eleven coal chars are studied in a laboratory scale fixed bed reactor using a simulated flue gas for NO reduction. XPS are applied to evaluate the distributions of different surface carbon-oxygen complexes on char surface and distinguish their roles in the reaction of NO with carbon in the presence of oxygen. BET and TEM have been employed to characterize the textural and structural properties of these coal chars. It is found that thermally relatively stable C–O species play a more important role compared with R2 CO and O–CO. Enrichment of surface C–O species on char surface can enhance NO reduction and simultaneously control CO formation. Activated carbon and H2 O2 -modified activated carbon are also investigated to verify this point. Two different reaction mechanisms, i.e., surface carbon-oxygen complexes involved reactions and directly burn-off unoccupied surface, are put forward to explain different performance exhibited by the samples examined in this work.